FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN IBU NIFAS TENTANG PEMBERIAN ASI EKSKLUSIF DI PUSKESMAS LUBUK BAJA KOTA BATAM - Sridewi, Dahlia; Mona, Silvia (Universitas Batam, 2020)
Learning achievement is a term that indicates a degree of success in the learning process. High or low achievement that can be achieved by someone in learning is influenced by several factors where these factors are related to one another, the low learning achievement caused by several factors such as motivation, interest, and social environment will have an impact on unsatisfactory GPA. Because in the world of work requires people with the best graduate grades to benefit in a company. The purpose of this study was to determine the factors associated with learning achievement. This type of research uses analytic surveys with Cross Sectional approach. This research collection includes all students in level 1 consisting of 84 students, with a sample of 74 respondents, using the Chi-Square analysis technique. Research using Google form. From the results of the study there were 40 respondents (81.6%) with high motivation achieving very satisfying learning achievement. Chi-Square statistical test results obtained p-value 0,000 <0.05, then there is a relationship between motivation and learning achievement. From 45 respondents (78.9%) with high interest in achieving very satisfying learning achievement Chi-Square statistical test results obtained p-value 0,000 <0.05, so there is a relationship between interest and learning achievement. Of the 48 respondents (70.6%) with a high social environment achieved very satisfying learning achievements. Chi-Square statistical test results obtained p-value 0.001 <0.05, then there is a relationship between the social environment and learning achievement. The conclusion of this study is that there is a relationship between motivation and learning achievement, the relationship between interest in learning achievement, and the relationship between social environment and learning achievement of first-year medical students at Batam University in 2019.